Application of synthetic data for analytics with generative ai and vector search capabilities - Saveliev, Roman; Dendiuk, Mykhailo (Комп’ютерне моделювання та інформаційні технології, 2023)
This research investigates the transformative potential of Generative Artificial Intelligence (Generative AI) in the realm of data analytics within distributed systems. Specifically, we explore the utilization of Generative AI models, such as Generative Adversarial Networks, to generate synthetic datasets that closely mimic real-world data. Our focus extends to the innovative application of vector search within these synthetic datasets, examining its implications for data analytics and exploring the ethical considerations surrounding the use of synthetic data.